2019
DOI: 10.1242/dev.170498
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cdx factors in early mesodermal fate decisions

Abstract: Murine cardiac and hematopoietic progenitors are derived from Mesp1 + mesoderm. Cdx function impacts both yolk sac hematopoiesis and cardiogenesis in zebrafish, suggesting that Cdx family members regulate early mesoderm cell fate decisions. We found that Cdx2 occupies a number of transcription factor loci during embryogenesis, including key regulators of both cardiac and blood development, and that Cdx function is required for normal expression of the cardiogenic transcription factors Nkx2-5 and Tbx5. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 110 publications
(247 reference statements)
2
19
0
Order By: Relevance
“…It has been demonstrated that Cdx2 is the predominant Cdx gene expressing the AGM HE, while the expression of other Cdx genes is substantially lower ( Gao et al, 2018 ). Cdx2 deficiency caused the most significant impairment in blood production from mouse ESCs ( Wang et al, 2008 ) and Cdx1-Cdx2 compound conditional null mice failed to produce any blood at embryonic day (E)11.5 ( Foley et al, 2019 ), suggesting that among the Cdx family, Cdx2 is the most critical factor required for establishing hematopoiesis. Our finding of the direct regulation of CDX2 expression by SOX17 provides an insight into the mechanisms responsible for establishing a CDX-HOXA pathway required for the formation of definitive AGM-like HE and lympho-myeloid hematopoiesis from hPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Cdx2 is the predominant Cdx gene expressing the AGM HE, while the expression of other Cdx genes is substantially lower ( Gao et al, 2018 ). Cdx2 deficiency caused the most significant impairment in blood production from mouse ESCs ( Wang et al, 2008 ) and Cdx1-Cdx2 compound conditional null mice failed to produce any blood at embryonic day (E)11.5 ( Foley et al, 2019 ), suggesting that among the Cdx family, Cdx2 is the most critical factor required for establishing hematopoiesis. Our finding of the direct regulation of CDX2 expression by SOX17 provides an insight into the mechanisms responsible for establishing a CDX-HOXA pathway required for the formation of definitive AGM-like HE and lympho-myeloid hematopoiesis from hPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in mice, ectopic Tbx5 expression was observed in the yolk sac of Cdx1/2 compound conditional null mutants at the expense of hematopoietic markers [123]. Current evidence supports a mechanism of action for Cdx genes in which they stably repress cardiac loci in early Mesp1+ mesoderm by directly recruiting the SWI/SNF epigenetic silencing complex [123]. Thus, the expression of Cdx biases these progenitors to hematopoietic lineages at the expense of cardiac lineages.…”
Section: Leukemiamentioning
confidence: 95%
“…In zebrafish, the tbx5a -expressing anterior cardiogenic mesoderm was expanded in cdx1a/4 mutants [122]. Similarly, in mice, ectopic Tbx5 expression was observed in the yolk sac of Cdx1/2 compound conditional null mutants at the expense of hematopoietic markers [123]. Current evidence supports a mechanism of action for Cdx genes in which they stably repress cardiac loci in early Mesp1+ mesoderm by directly recruiting the SWI/SNF epigenetic silencing complex [123].…”
Section: Leukemiamentioning
confidence: 99%
“…5). VIA consistently uncovers the bifurcating lineages using both single-cell transcriptomic (scRNA-seq) and chromatin accessibility (scATAC-seq) information [26][27][28] , as well as their data integration (see "Methods" for data integration using Seurat). Other methods that are also applicable to non-transcriptomic data, fail to uncover the two main lineages.…”
Section: Cd79bmentioning
confidence: 99%
“…Although PCA is a common step in analyzing transcriptomic data in order to strengthen the signal in the data, we also show that in-principle, VIA can handle 1000 s of genes as direct inputs without any PCA at all (Supplementary Note 5 and Figs. [27][28][29]. We showcase the scalability of sample size by analyzing the fine-grained developmental sub-trajectories in the 1.3million-cell mouse organogenesis atlas in terms of fast runtime and preservation of global cell-type connectivity, which is otherwise lost in existing TI methods.…”
mentioning
confidence: 99%